Differences in Motor Abilities in Preschool Boys - Đorđević, Marija M.; Dašić, Stefan S. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2022)
The aim of this study was to determine the differences in motor abilities in preschool boys, depending on the level of their physical activity. The total sample consisted of 30 boys aged between 6 and 7, who attended kindergartens "Plavi zec" and "Kolibri" in the city of Paracin. The sample was divided into two subsamples. The first subsample consisted of 15 boys who, in addition to physical activity in the kindergarten (according to the plan and program implemented by the preschool institution), were, in the previous six months, members of the soccer club "Vuk" from Paracin. The second subsample consisted of 15 boys who did not have additional (organized) physical activity outside the plan and program implemented in the preschool institution. Motor abilities were determined by using a standardized battery of motor tests, taken from the research of Bale and Popovic (2007). Running speed (20 meter run from a standing start), frequet arm movement (arm taping), explosive leg strength (standing depth jump), explosive arm strength (throwing a 1kg medicine ball) and body coordination (polygon backwards) were tested. Differences in motor abilities were calculated by T-test and by using a small and indipendent sample size. The results of this study indicate that boys who were involved in additional physical activities.
Keywords: speed; explosive strength; coordination; preschool age